Effect of Temperature on Allelopathic Interactions Between Copepods (Copepoda) and Rotifers (Rotifera) - Ana Nayeli López-Rocha; S. S. S. Sarma; S. Nandini (Diversity)
The role of abiotic factors in the allelopathic interactions between copepods and rotifers is poorly documented. Temperature has a marked effect on the metabolism of zooplankton. Therefore, the release of allelochemicals by copepods and the response of rotifers to them may change as temperatures increase. Here, we tested the effect of two temperatures (20 and 25 °C) on the population growth of Brachionus havanaensis cultured on a conditioned medium (CM) of Arctodiaptomus dorsalis and Eucyclops sp. The CM was obtained daily, separately, for the males and females of both copepod species at a density of 0.1 ind. mL−1 for 24 h prior to experiments. In the controls and CM treatments, higher temperatures had a stimulatory effect on the population growth and the rate of population increase (r) of B. havanaensis. At 25 °C, the CM from the females and males of A. dorsalis caused >30% increase in r, but for the CM from Eucyclops sp., this effect was lower (<21%). At 20 °C, the r in the controls and CM treatments was not significantly different. The morphometry of B. havanaensis varied depending on the treatments. Compared to controls, longer loricae were recorded in the CM of male A. dorsalis at both temperatures. However, in the CM of female calanoids, longer rotifers were observed only at higher temperatures. At 20 °C, the CM from Eucyclops produced smaller loricae. The relationship between the lorica length and width of rotifers showed a linear relation but the slope differed among the treatments.